Direct growth of single-layer terminated vertical graphene array on germanium by plasma enhanced chemical vapor deposition. (December 2019) - Al-Hagri, Abdulrahman; Li, Ru; Rajput, Nitul S.; Lu, Jin-You; Cong, Shan; Sloyan, Karen; Almahri, Mariam Ali; Tamalampudi, Srinivasa Reddy; Chiesa, Matteo; Al Ghaferi, Amal
Abstract: Vertically aligned graphene nanosheet arrays (VAGNAs) exhibit large surface area, excellent electron transport properties, outstanding mechanical strength, high chemical stability, and enhanced electrochemical activity, which makes them highly promising for application in supercapacitors, batteries, fuel cell catalysts, etc. It is shown that VAGNAs terminated with a high-quality single-layer graphene sheet, can be directly grown on germanium by plasma-enhanced chemical vapor deposition without an additional catalyst at low temperature, which is confirmed by high-resolution transmission electron microscopy and large-scale Raman mapping. The uniform, centimeter-scale VAGNAs can be used as a surface-enhanced Raman spectroscopy substrate providing evidence of enhanced sensitivity for rhodamine detection down to 1 × 10 −6  mol L −1 due to the existed abundant single-layer graphene edges. Graphical abstract: Vertically aligned graphene nanosheet arrays (VAGNAs) terminated with high-quality single-layer graphene has been directly grown on germanium surface by plasma enhanced vapor deposition at low temperature. The uniform, large area VAGNAs can be used as efficient surface-enhanced Raman spectroscopy substrate (SERS) with sensitivity down to 1 × 10 −6  M rhodamine due to the existed abundant single-layer graphene edges.Image 1